2016
DOI: 10.1515/johh-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Inlet effects on roll-wave development in shallow turbulent open-channel flows

Abstract: The present work investigates the effect of the flow profile induced by an inlet condition on the roll-wave evolution in turbulent clear-water flows. The study employs theoretical and numerical analyses. Firstly, the influence of the inlet condition on the spatial evolution of a single perturbation in a hypercritical flow is examined through the expansion near a wavefront analysis. The results show that an accelerated unperturbed profile reduces the disturbance spatial growth. A decelerated profile causes an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…The roll wave of flow on slopes is initially produced by surface tension. As the water depth and flow velocity increase, the surface tension effect weakens and a "capillary roll wave" is gradually transformed into an "inertial roll wave" (Campomaggiore et al 2016). The inertial roll wave originates from the inertial instability (Brock 1969;Logan and Iverson 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roll wave of flow on slopes is initially produced by surface tension. As the water depth and flow velocity increase, the surface tension effect weakens and a "capillary roll wave" is gradually transformed into an "inertial roll wave" (Campomaggiore et al 2016). The inertial roll wave originates from the inertial instability (Brock 1969;Logan and Iverson 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Because the roll wave has significant impacts on the origination and transportation of sediments on the slope, its prediction is of great interest to the field of environmental engineering (Campomaggiore et al 2016). Harold (1925) and Cornish (1934) were the first to study the roll wave.…”
Section: Introductionmentioning
confidence: 99%
“…For very small p values, the governing equations may be linearized in the neighborhood of the uniform flow condition and analytically solved. The solution is known for the clear-water case, both for constant (Supino, 1960) or variable (Campomaggiore et al, 2016b) friction factor, and it has been previously used as a benchmark for numerical methods aimed to reproduce roll-waves development (Zanuttigh and Lamberti, 2002;Campomaggiore et al, 2016b). This solution has been herein further extended to account for the features of the present flow model, namely the momentum coefficient and the different rheological behavior.…”
Section: Numerical Methods Validationmentioning
confidence: 99%
“…For clear-water flows in turbulent regime, it is widely accepted that the essential features of natural rollwaves train may be reproduced by forcing the shallow water model with a random noise at the inlet. It was shown that both fully hyperbolic (Zanuttingh and Lamberti, 2002;Campomaggiore et al, 2016b) or diffusive (Chang et al, 2000;Huang and Lee, 2015a,b;Cao et al, 2015) models are able to predict the main properties of the roll-waves spatial evolution experimentally observed by Brock (1967). In particular, Brock (1967) observed that the initial development of the phenomenon showed an exponential growth of the perturbations.…”
Section: Introductionmentioning
confidence: 93%
“…Through time, chiefly in the last 15 years, the roll wave phenomenon has been reported in the physics literature (Liu & Mei, 1994;Liu & Gollub, 1994;Needham & Merkin, 1987;Hwang & Chang, 1987;Gao et al, 2003), in chemistry (Holmås, 2010), in engineering (He et al, 2020;Mcardell, 2016) and in applied mathematics (Razis et al, 2019;Campomaggiore et al, 2016), under three self-complementary branches: mathematical, numerical and experimental modelling. This reaffirms the multiinter-transdisciplinary aspect of the subject, reflecting in the opportunity/possibility to gather around different researchers (Balmforth, 2011), (e) Channelized Achumani River, La Paz (Ponce & Guzmán, 2019).…”
Section: Introductionmentioning
confidence: 99%